The ability of Students in Pronunciation English Palatal Alveoral Fricative and Palatal Alveoral Affricative Consonant at Ninth Grade of Junior High School 17 Jambi City - Suci Wulandari; Efa Silfia; Kartika Dewi (JELT: Journal of English Language Teaching, 2022)
Pronunciation is one of the components in speaking ability. This component plays very important role in communication, because by pronouncing the English words correctly students are able to avoid misunderstanding when they are speaking, therefore to be able to say English words fluently and correctly, the students should have good mastery in pronunciation especially in pronouncing English palatal alveolar fricative and affricative consonant sounds. This research is aimed at describing students” ability to pronounce English palatal alveolar fricative and affricative consonants (∫ and t∫) and find out in which position (initial, medial, and final) are the most difficult to pronounce. The design of this research was descriptive quantitative method approach. This research was conducted Junior High School Number 17 Kota Jambi in January 2022. in conducting this research, this research administered the pronunciation test one time, the. The population of this research was the ninth-grade students at SMPN 17 Jambi City in academic year 2021-2022, the total number of them were 340 students. As the sample was the ninth-grade students, they consist of 10 students. This research used purposive sampling technique in taking the sample if this research. The result of this research showed that on the test there were 4 students belong to very good categories, 2 student belongs to good categories, 3 students belong to fair categories, 1 student belongs to weak category and none of the student belong to poor category. the ability of the students in pronouncing the English palatal alveolar fricative (∫) and (t∫) affricative consonant was 78%, this is categorized as good. The students” ability in pronouncing sound (∫) belongs to very good category (85%) and sound (t∫) belongs to good category (73%)